The Lifestyle of Hypertensive People and its Health Effects - Pandey, Naranath (Madhyabindu Journal, 2022)
Lifestyle changes have brought many problems in people like hypertension, hyperacidity, diabetes, heart disease, liver disease, kidney disease, cancer etc. Therefore, this study has been done to find out the effect of lifestyle on some people with high blood pressure in Kawasoti Nawalpur. This study was conducted using a convenient survey method and using an interview schedule. In this study, a sphygmomanometer and stethoscope were used to find out the blood pressure and a weighing machine and measuring tape were used to find out the body mass index (BMI) of the hypertensive people.A study of 320 people found that 108 people had high blood pressure. After analyzing the data, found that the analyzing main causes of hypertension in hypertensive people are; obesity (38.89%), alcohol consumption (55.56%), smoking (81.48%), more salt and junk food intake (74.07%), and living a sedentary lifestyle (35.19%) etc. The effects of hypertension on hypertensive people are; headache (82.40%), having trouble sleeping (50.92%), Dizziness (49.07%), shortness of breath (13.89%), epistaxis (8.33%), and feel palpitation (33.33%). They have tried to reduce hypertension by losing weight by doing many tasks like fasting once a week (68.51%), yoga or physical exercise (33.33%), reducing alcohol drinking and smoking habits (85.18%) etc. So, after finding out the main causes of hypertension, the researcher wants to suggest to hypertensive people to change their lifestyle including losing weight.